Associations between Parenting Style and Nutritional Knowledge on Stunting in Children Aged 24-60 Months in Ketang Health Center, East Nusa Tenggara, Indonesia - Heribertus Handi Erick (Masters Program in Public Health, 2023)
Background: Stunting is a condition of children under five with a z-score of less than -2 standard deviation (stunted) and less than -3 standard deviation (severely stunted). Interventions to accelerate stunting prevention require intervention and coaching, such as knowledge and parenting of toddlers in the community. This study aimed to determine the relationships between knowledge, and stunting in children aged 24-60 months.Subjects and Method: This was a retrospective cross-sectional study conducted in the Ketang Health Center, East Nusa Tenggara, Indonesia. A total of 60 children aged 24-60 months and their mothers was selected using purposive sampling. The independent variables were parenting and nutritional knowledge. The dependent variable was stunting. The instruments of this study were height measurement tools, knowledge, and parenting questionnaires. The data were analyzed using multiple logistic regression.Results: Children who have mothers with poor parenting are 0.15 times more stunted than mothers with good parenting. Nutrition knowledge is 0.04 times less likely to be stunted than mothers with good nutrition knowledge.Conclusion: Mothers with poor parenting and nutritional knowledge increase the risk of stunting. Keywords: Nutritional knowledge, parenting, stunting. Correspondence:Heribertus Handi. Nursing Study Program, Universitas Katolik Indonesia Santu Paulus Ruteng. Jl. Jenderal A. Yani No. 10, Langke Rembong, East Nusa Tenggara. Email: herihandi84@gmail.com. Mobile: 085236119205.